An integrated framework for planning successful complete streets: Determinative variables and main steps - Dehghanmongabadi, Abolfazl; Hoskara, Sebnem (Taylor & Francis Inc, 2022)
The development of an integrated framework for planning successful complete streets and leading to a sustainable transportation sector begins with a clarification of the determinative variables and steps. A review of a broad selection of documents related to complete streets and active modes of transportation resulted in distinct lists of variables taken from each subject. Though the literature categorized built-environment variables for both subjects, social-context variables were found to be lacking in the complete streets documents. The integration of the variables from the two sets of sources formed a comprehensive list of effective determinative variables. Together, with the identification of the socially- and physically-inclusive variables, this research recommends use of an integrated framework for planning successful complete streets toward enhancing the level of sustainable mobility inside communities.
Keywords: Active transportation; complete streets; complete streets planning steps and determinative variables; sustainable mobility